An overview on Cloud Security and Proposed Solutions (International Journal of Engineering and Computer Science, 2017)
Cloud computing has revolutionized the world of computing in the last few years. The benefits such as reduced costs, rapid application deployment, and elastic resources, have made many organizations to utilize cloud resources or host much of their data in the cloud. Recent studies shown that more than 70 percent of the world’s businesses now operate some of their operations in the cloud. But the security of the data stored in cloud is the major concern. This paper gives a vogue idea about the cloud security threads and its proposed solutions.